Designing institutions for diversity - Igor Letina; Armin Schmutzler (University of Zurich, Department of Economics, 2015)
This paper analyzes the design of innovation contests when the quality of an innovation depends on the research approach of the supplier, but the best approach is unknown. Diversity of approaches is desirable because it generates an option value. In our main model with two suppliers, the buyer optimally uses a bonus tournament, where suppliers can choose between a low bid and a high bid. This allows the buyer to implement any level of diversity with the lowest revenue for the suppliers. We also compare other common contests, in particular, fixed-prize tournaments and auctions. Like bonus tournaments, auctions implement the socially optimal diversity, but usually with higher rents for the suppliers. Fixed-prize tournaments implement insufficient diversity, but may nevertheless be preferred by the buyer to auctions because of lower supplier rents.
Keywords: L14; L22; L23; 330; contests; tournaments; auctions; diversity; procurement